Spinal Cord Injury at Birth, Expected Medical and Health Complexity in Chronic Injury Guided Anew by Activity-Based Restorative Therapy: Case Report - Leon Machado, Laura; Noonan, Kathryn; Bickel, Scott; Singh, Goutam; Brothers, Kyle; Calvery, Margaret; Behrman, Andrea L. (Frontiers in Psychology, 2022)
As infancy is characterized by rapid physical growth and critical periods of development, disruptions due to illness or disease reveal vulnerability associated with this period. Spinal cord injury (SCI) has devastating consequences at any age, but its onset neonatally, at birth, or within the first year of life multiplies its impact. The immediate physical and physiological consequences are obvious and immense, but the effects on the typical trajectory of development are profound. Activity-based restorative therapies (ABRT) capitalize on activity-dependent plasticity of the neuromuscular system below the lesion and when provided to children with SCI aim to improve the child’s neuromuscular capacity, health and quality of life. This is a report of an infant with a cervical SCI at birth resulting in paralysis of leg and trunk muscles and paresis of arm and hands who was enrolled in an ABRT program at 3 years of age. After 59 sessions of ABRT, the child demonstrated significant improvements in trunk control and arm function, as well as social and emotional development. Despite the chronicity of injury and low expectations for improvement with therapeutic interventions, ABRT had a positive impact on the child’s physical capacity and provided benefits across multiple developmental domains.